Antepartum Dalteparin Versus no Antepartum Dalteparin for the Prevention of Pregnancy Complications in Pregnant Women With Thrombophilia (TIPPS): A Multinational Open-label Randomized Trial. Issue 4 (December 2015) - Rodger, M.A.; Hague, W.M.; Kingdom, J.; Kahn, S.R.; Karovitch, A.; Sermer, M.; Clement, A.M.; Coat, S.; Chan, W.S.; Said, J.; Rey, E.; Robinson, S.; et al.
Abstract : ( Lancet. 2014;384(9955):1673–1683)